2023
DOI: 10.1039/d3fd00063j
|View full text |Cite
|
Sign up to set email alerts
|

Gating ion and fluid transport with chiral solvent

Abstract: The development of modern membranes for ionic separations and energy-storage devices such as supercapacitors depends on the description of ions at solid interfaces, as is often provided by the electrical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Further work by Polster et al and Souna et al described the formation of a lipid-like bilayer of MeCN at a solid silica interface, and the resulting effective surface potential arising as electrolyte ions interact with it. Remarkably, Silva et al reported that this organization of solvent is dependent on chirality, with enantiopure propylene carbonate (PC) exhibiting a lower positive surface potential than racemic PC. In our previous work, we reported the unusual behavior of bare quartz nanopipettes in aprotic solvent as a function of decreasing supporting electrolyte concentration, showing that under specific electrolyte conditions, accumulation of aprotic solvent and the subsequent formation of double-junction diodes within the nanopore gives rise to unexpectedly high rectification ratios .…”
Section: Introductionmentioning
confidence: 99%
“…Further work by Polster et al and Souna et al described the formation of a lipid-like bilayer of MeCN at a solid silica interface, and the resulting effective surface potential arising as electrolyte ions interact with it. Remarkably, Silva et al reported that this organization of solvent is dependent on chirality, with enantiopure propylene carbonate (PC) exhibiting a lower positive surface potential than racemic PC. In our previous work, we reported the unusual behavior of bare quartz nanopipettes in aprotic solvent as a function of decreasing supporting electrolyte concentration, showing that under specific electrolyte conditions, accumulation of aprotic solvent and the subsequent formation of double-junction diodes within the nanopore gives rise to unexpectedly high rectification ratios .…”
Section: Introductionmentioning
confidence: 99%